Description and biology of Euborellia arcanum sp. nov., an alien earwig occupying greenhouses in Germany and Austria (Dermaptera: Anisolabididae) - Matzke, Danilo; Kocarek, Petr (Zootaxa, 2015)
Greenhouses in botanical or zoological gardens are home to dozens of species of invertebrates that were introduced alongside plants or potting soil. Our study presents the description of an alien species of earwig, Euborellia arcanum sp. nov., found in tropical greenhouses in Leipzig and Potsdam (Germany) and in Vienna (Austria), including information about its biology in breeding culture. The species was most likely introduced into Europe by way of plants or plant matter from Florida, but the region of its natural habitat is unknown. The sequence of the mitochondrial gene cytochrome c oxidase subunit I (COI) was also evaluated and added to GenBank as a DNA barcode for further identification.